2018
DOI: 10.1371/journal.pone.0203812
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting soil microbial biomass and functional diversity with the application of organic amendments in three contrasting cropland soils during a field experiment

Abstract: The effects of soil type and organic material quality on the microbial biomass and functional diversity of cropland soils were studied in a transplant experiment in the same climate during a 1-year field experiment. Six organic materials (WS: wheat straw, CS: corn straw, WR: wheat root, CR: corn root, PM: pig manure, CM: cattle manure), and three contrasting soils (Ferralic Cambisol, Calcaric Cambisol and Luvic Phaeozem) were chosen. At two time points (at the end of the 1st and 12th months), soil microbial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 69 publications
4
38
0
Order By: Relevance
“…He et al [50] presented results indicating a reduction in AOA diversity in the soil as a consequence of lowering the soil pH which is caused by the use of nitrogen fertilizers. On the other hand, the addition of organic fertilizers and organic matter resulted in an increase in the AOA population on account of the greater bioavailability of C [51]. In this paper, we present results which indicate a positive effect of using the tested EOM on the diversity of the AOA population.…”
Section: Discussionmentioning
confidence: 67%
“…He et al [50] presented results indicating a reduction in AOA diversity in the soil as a consequence of lowering the soil pH which is caused by the use of nitrogen fertilizers. On the other hand, the addition of organic fertilizers and organic matter resulted in an increase in the AOA population on account of the greater bioavailability of C [51]. In this paper, we present results which indicate a positive effect of using the tested EOM on the diversity of the AOA population.…”
Section: Discussionmentioning
confidence: 67%
“…Differential usages of C-sources were observed for gorse-and Scotch broom-amended soils if compared to control treatments, as indicated by the correspondence analysis separation. Recently, Li et al [45] have confirmed that these changes are measurable using BIOLOG analysis at only one month after the applications of the amendment to the soil. For gorse, the preference for specific carbohydrate substrates like β-methyl-D-glucoside was more clearly linked to control soil samples, whereas the phenolic compounds (C-substrates 18 and 19) were represented close to the foliage-amended soils.…”
Section: Discussionmentioning
confidence: 91%
“…One way to determine functional diversity is community level physiological profiling (CLPP) with the application of plates (BIOLOG ® , Hayward, CA, USA) coated with various carbon sources and dedicated to specific groups of microorganisms. As a result, a characteristic and unique utilization pattern of the C-substrates called "metabolic fingerprinting" is obtained [130,131]. For the evaluation of the catabolic abilities of soil bacterial and fungal communities, BIOLOG ECO and BIOLOG FF microplates were used, respectively [132].…”
Section: Community Level Physiological Profiling (Clpp)mentioning
confidence: 99%